Standardizing Second-Trimester Medical Termination: Effects on Clinical Outcomes - Wyatt, Michelle A.; Tolcher, Mary Catherine (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate length of induction and postdelivery complications before and after implementation of a standardized approach to second-trimester medical termination of pregnancy.Study Design This was a retrospective cohort study of all women undergoing medical termination of pregnancy between 130/7 and 266/7 weeks of gestation at a single, academic institution from July 1, 2012, through June 30, 2015. The primary outcome was the time from the start of induction of labor to delivery of the fetus. Postdelivery complications including the need for dilation and curettage (D&C), blood transfusion, and readmission to the hospital were secondary outcomes of interest.Results A total of 62 women met inclusion criteria; 38 before and 24 after the intervention. There were no differences in measured baseline characteristics (p > 0.05). There was a significant decrease in induction time after the intervention (12.3 compared with 8.6 hours, p = 0.031). There was no significant difference in rates of D&C or other measured complications (p > 0.05).Conclusion Implementation of a standardized clinical guideline for second-trimester medical termination was associated with a decrease in length of induction. There was no significant difference in need for D&C or postdelivery complications; however, we were underpowered for these secondary outcomes.
Keywords: labor induction; second-trimester induction; termination of pregnancy; misoprostol induction